SELEKSI BERBANTUKAN MARKA MOLEKULER UNTUK PEMBENTUKAN CALON VARIETAS PADI TURUNAN ESENSIAL SITU PATENGGANG - Siti Yuriyah; Dwinita Wikan Utami; Siti Nurani; Anggiani Nasution; Puji Lestari; Ahmad Dadang; Suwarno Suwarno (Research Center for Biology-Indonesian Institute of Sciences, 2019)
The utilization of molecular marker technology for Blast (Pyricularia grisea) resistance in rice breeding could accelerate and improve the precision of selection. This study aimed to identify and to select the BC3F2 progenies from Situ Patenggang and the opted Blast Monogenic Lines based on their resistance to blast disease in green house and field using molecular characterization. A total of 200-300 BC3F2 population strains resulted in 4 crosses between Situ Patenggang varieties and Monogenic Varieties IRBLta2-Re, IRBLkp-k60, IRBLi-F5 and IRBLa-A were used as total genetic material in the study. Blast resistance assay was initially carried out in a greenhouse and further selection was conducted in the endemic blast area, Sukabumi. The selected Molecular marker was STS (Sequence Taq Sites) marker for foreground selection and 384-SNPs (Single Nucleotide Polymorphism) chip for background selection. The number of lines from each cross was selected by greenhouse assay i.e: 25 lines derived from Situ Patenggang/IRBLta and Situ Patenggang/IRBLkp, 21 plants for crossing Situ Patenggang/IRBLi, and 22 plants for Situ Patenggang/IRBLa-A. The results of field experiment revealed that blast resistance response of the selected lines was varied from 0 to 5. Lines of foreground were successfully selected using STS markers specified for Pii, Pita, Pikp and Pia genes. As for the background selection by SNPs markers, some lines carried the recurrent parent genetic background, Situ Patenggang. Overall, 20 resistance lines that harbored the target genes and Situ Patenggang background were obtained. Further observation was entailed to these twenty selected lines in order to attain promising lines candidate for blast resistance.